Diagnostic value of fecal B cell activating factor in patients with abdominal discomfort. (5th August 2019) - Xie, C; Quan, R; Wang, L; Chen, C; Yan, W; Fu, Y
Summary: Fecal calprotectin has successfully been widely recommended as a sensitive biomarker of inflammatory bowel diseases (IBD). Recently, we have identified an excellent new fecal biomarker, B cell activating factor (BAFF), as being as effective as fecal calprotectin for diagnosing intestinal inflammation. In this study, a total of 230 patients with abdominal discomfort were prospectively enrolled and fecal samples were collected within 24 h before the endoscopic examinations. We show that fecal BAFF levels were significantly higher in patients with ulcerative colitis (median = 1549 pg/g, P < 0·0001), Crohn's disease (median = 735 pg/g, P < 0·0001), gastric cancer (median = 267 pg/g, P < 0·0001) and colorectal cancer (median = 533 pg/g, P < 0·0001) than those in healthy groups (median = 61 pg/g), while the values of which in patients with gastric polyps, colorectal polyps, esophagitis/gastritis/duodenitis and peptic ulcer were in the range of healthy individuals ( P > 0·05). An optimal cut-off value at 219·5 pg/g of fecal BAFF produced sensitivity, specificity, positive predictive and negative predictive values of 85, 91, 84 and 92%, respectively, for IBD or carcinoma. Our results therefore indicate a potential role for fecal BAFF as a sensitive screening parameter for IBD and gastrointestinal carcinoma, as well a useful tool to select patients with abdominal discomfort for further endoscopic examinations. Graphical Abstract: